The Elves and the Shoemaker - Southgate, Vera (London : Lady bird ltd)
A poor hardworking shoemaker had so little leather that he could only make a single pair of shoes. One evening, leaving the pair with the work unfinished, he went to bed and commended himself to God. After waking up the following day and saying his prayers, he found the shoes finished and perfectly well-made on his workbench. A customer soon entered the store and offered more than the usual price, for he was fond of the pair. The shoemaker uses the money to buy leather for more shoes which, after cutting, he also leaves overnight. Again the materials are made into beautiful shoes by morning. In this manner, his situation improves until he is comfortable again. One evening, shortly before Christmas, the shoemaker said to his wife, "Why don't we stay up tonight and see who is giving us this helping hand," and his wife agreed. Hiding in the corner of the room, they saw two little men working quickly and nimbly on the shoes, then running away after their work was finished.[1] The next morning, his wife said, "The little men have made us wealthy. We must show them our thanks. They are running around with nothing on, freezing." She proposed to make clothes, and the shoemaker agreed to make a pair of shoes for each of them. The two of them did not stop until they had finished the work, then hid themselves again. The following night, the couple saw the little men delighted as they tried the beautiful little clothes and shoes; they danced out of the house and never returned, but the shoemaker prospered in his business
Fiction English book
Keywords: English - Fiction Book